Trends in practical applications of agents and multiagent systems : 10th International conference on practical applications of agents and multi-agent systems - Rodríguez, Juan M. Corchado (Advances in Intelligent and Soft Computing, 2012)
PAAMS, the International Conference on Practical Applications of Agents and Multi-Agent Systems is an evolution of the International Workshop on Practical Applications of Agents and Multi-Agent Systems. PAAMS is an international yearly tribune to present, to discuss, and to disseminate the latest developments and the most important outcomes related to real-world applications. It provides a unique opportunity to bring multi-disciplinary experts, academics and practitioners together to exchange their experience in the development of Agents and Multi-Agent Systems.   This volume presents the papers that have been accepted for the 2012 in the workshops: Workshop on Agents for Ambient Assisted Living, Workshop on Agent-Based Solutions for Manufacturing and Supply Chain and Workshop on Agents and Multi-agent systems for Enterprise Integration.